CONTENT ANALYSES ON THE USE OF TECHNOLOGY IN DYSLEXIA: THE ARTICLES IN THE WEB OF SCIENCE DATA BASE - Idris Adamu; Emrah Soykan (Informascope, 2019)
Articles published in web of Science between 2014 and 2019 (March) were screened in this research. This is because of its respectable position in the field of technology and peer-reviewed secured structure of this database. From a total of 56 articles within the scope of the screening 46 articles were included in the study. Through this research, new trends on technology usage in dyslexia activities in recent years will be determined and a new way will be shown for researchers. "Technology in dyslexia" keywords used during researching process and all the articles with "technology in dyslexia" keywords were included in this study. As a result of this research, it is determined that the most studies in the field of technology in dyslexia were published in 2018 in USA, UK, Spain, and Pakistan.  Particularly children students were selected as the sample group of the researches. It is emerged that, questionnaires research was used maximum as a research instrument. Quantitative data collection tools were used most as a means of data collection medicals area as the research fields through traditional teaching method. It was emerged that assistive technology is the most widely used field in technology in dyslexia. It is seen that optometric neuropsychological assessments, digital tools and adaptive mobile learning as devices were used in the most researches. Lecture-based method is seen to be used as the teaching method in the present study. Keywords: Technology, Dyslexia, Assistive Technology and Web of Science.